Studi Komparasi Hasil Belajar Menggunakan Model Group Investigation dengan Model Picture And Picture Pada Mata Pelajaran Sains Kelas IV Sekolah Dasar - A Arsil; Abd Haris (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2016)
This study aims to determine the differences in the average results of learning science the subject matter of the structure and function of plants between students whose learning uses a group investigation learning model with a model of picture and picture. This research includes field research, with the method used is comparative causal. The population of this study were all fourth grade students of SDN 45/1 Sridadi in the first semester of the 2014/2015 academic year, consisting of IV-A classes with 25 students, IV-B classes with 24 students. So the total population was 47 participants student. Because the population is less than 100, the entire population is sampled, with class IV-A consisting of 25 students as experimental class B and class IV-B consisting of 24 students as experimental class A. Data is collected by documentation method and test. The collected data were analyzed using statistical analysis of test differences in the average experimental class 1 (group investigation) and experimental class 2 (picture and picture) with the analysis of the two-party t-test test. Based on the results of the study it can be concluded that: the average science learning outcomes in the subject matter of plant structure and function of IV-A class students with the group investigation model is 84.44, while the average mathematics learning outcomes of students studying with a model of picture and picture is 77.29.